Functional redundancy of the two 5-hydroxylases in monolignol biosynthesis of Populus trichocarpa: LC–MS/MS based protein quantification and metabolic flux analysis - Jack P. Wang; Christopher M. Shuford; Quanzi Li; Jina Song; Ying-Chung Lin; Ying-Hsuan Sun; Hsi-Chuan Chen; Cranos M. Williams; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Effects of the fungicide metiram in outdoor freshwater microcosms: responses of invertebrates, primary producers and microbes - Ronghua Lin; Laura Buijse; Mauricio R. Dimitrov; Peter Dohmen; Sujitra Kosol; Lorraine Maltby; Ivo Roessink; Jos A. Sinkeldam; Hauke Smidt; René P. A. Van Wijngaarden; Theo C. M. Brock (Ecotoxicology, 2012)

Phosphorus availability and rice grain yield in a paddy soil in response to long-term fertilization - Z. M. Lan; X. J. Lin; F. Wang; H. Zhang; C. R. Chen (Biology and Fertility of Soils, 2012)

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Reemerging of enterovirus 71 in Taiwan: the age impact on disease severity - S.-M. Wang; T.-S. Ho; H.-C. Lin; H.-Y. Lei; J.-R. Wang; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A review of magnetic resonance imaging and diffusion tensor imaging findings in mild traumatic brain injury - M. E. Shenton; H. M. Hamoda; J. S. Schneiderman; S. Bouix; O. Pasternak; Y. Rathi; M.-A. Vu; M. P. Purohit; K. Helmer; I. Koerte; A. P. Lin; C.-F. Westin; et al. (Brain Imaging and Behavior, 2012)

Analysis of quantitative disease resistance to southern leaf blight and of multiple disease resistance in maize, using near-isogenic lines - Araby R. Belcher; John C. Zwonitzer; Jose Santa Cruz; Mathew D. Krakowsky; Chia-Lin Chung; Rebecca Nelson; Consuelo Arellano; Peter J. Balint-Kurti (Theoretical and Applied Genetics, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)